2019
DOI: 10.1175/jamc-d-18-0253.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Prediction of Midsummer Extreme Precipitation Days over Northeast China

Abstract: Northeast China (NEC) has sustained economic losses in recent years because of extreme precipitation events. Despite many efforts, it remains very difficult to predict these extreme events. In this study, we documented the characteristics of extreme precipitation days (EPD) over NEC and established a seasonal prediction model using a year-to-year increment (DY) approach. The results show that most of the EPD over NEC occurred during midsummer, along with large values concentrated over the Greater and Lesser Kh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Previous studies concerning summer precipitation in NEC have documented the influence of various atmospheric regimes, such as the East Asian monsoon systems (Sun et al 2007(Sun et al , 2017Cao et al 2018), blocking high at high latitudes (Yao and Dong 2000), cold vortex activities in NEC (Shen et al 2011), soil moisture content in northwest Eurasia (Zhu 2011), and the North Atlantic Oscillation (Sun and Wang 2012). For example, the wintertime Northern Hemisphere annual mode and North Pacific Oscillation both affect NEC precipitation during the following summer through modulation of the cold vortex (Liu et al 2002;He et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies concerning summer precipitation in NEC have documented the influence of various atmospheric regimes, such as the East Asian monsoon systems (Sun et al 2007(Sun et al , 2017Cao et al 2018), blocking high at high latitudes (Yao and Dong 2000), cold vortex activities in NEC (Shen et al 2011), soil moisture content in northwest Eurasia (Zhu 2011), and the North Atlantic Oscillation (Sun and Wang 2012). For example, the wintertime Northern Hemisphere annual mode and North Pacific Oscillation both affect NEC precipitation during the following summer through modulation of the cold vortex (Liu et al 2002;He et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Z. identified that the late spring precipitation anomaly in the Huang-Huai region is significantly connected with NEC summer precipitation via local soil moisture anomalies. Additionally, Han et al (2015) revealed a significant decrease in NEC precipitation after the late 1990s, and they attributed this decadal shift to the combined effects of the weakened Northeast Asian summer monsoon and changes in the Arctic sea ice area. Wang and He (2015) stated that the Pacific SST anomalies, the Arctic sea ice anomalies, and warming over both the European continent and the Caspian Sea contributed cooperatively to the severe drought in North China and Northeast Asia during summer 2014.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations